Imprints of environmental pollution on laterite/clay and groundwater of Eloor-Kalamassery Industrial Belt, Kerala State, India - V. Sobha M. Anish (Environmental Geology (2003) 44:914-918, 2003)
The role of laterites and clay in the adsorption of trace elements and consequent remediation of contaminated water from toxic elements has been studied. Laterite, clay and associated water samples from industrially and biologically polluted rivers and wells from Eloor-Kalamassery are analysed for Cr, Mn, Co, Ni, Cu, Zn, Cd, Pb, Bi, As, and Hg contents. The cation exchange capacity of the clay-organic matter components from the in situ and transported laterites and clay in differing environments of pollution are responsible for the reduction and depletion of toxic elements concentrated in the polluted water medium. Adsorption of toxic elements by laterite has further been corroborated by a simulation experiment conducted in the laboratory. An artificial laterite bed was prepared and water containing known amounts of Cr, Zn, Ni and Mn were allowed to flow overnight through the bed at uniform rate. Analysis of artificial laterite bed shows enrichment of Cr, Zn, Ni, Mn, indicating the absorbent properties of laterite.